2022
DOI: 10.1002/smll.202202060
|View full text |Cite
|
Sign up to set email alerts
|

An Unprecedented Fireproof, Anion‐Immobilized Composite Electrolyte Obtained via Solidifying Carbonate Electrolyte for Safe and High‐Power Solid‐State Lithium‐Ion Batteries

Abstract: The update of electrolytes from a liquid state to a solid state is considered effective in improving the safety and energy density of lithium‐ion batteries (LIBs). Although numerous efforts have been made, solid‐state electrolytes’ (SSEs) insufficient charge transfer capability remains a significant obstruction to practical applications. Herein, a fireproof and anion‐immobilized composite electrolyte is designed by solidifying carbonate electrolyte, exhibiting superior Li‐ion conductivity (11.5 mS cm−1 at 30 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The electrophilic/nucleophilic sites of DMSO, ClO 4 − and 18C6 were predicted via molecular electrostatic potential (MESP) calculation (Figure 1j). In a 18C6 molecule, the C−O−C groups exhibit nucleophilicity, while C−H and C−C groups show electrophilicity, which have electrostatic adsorption effect on negatively charged ClO 4 − anions to promote lithium salt dissociation [13] . Meanwhile, DMSO molecules with strong nucleophilic S=O groups are more involved in the first solvation sheath to bind with Li + [14] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrophilic/nucleophilic sites of DMSO, ClO 4 − and 18C6 were predicted via molecular electrostatic potential (MESP) calculation (Figure 1j). In a 18C6 molecule, the C−O−C groups exhibit nucleophilicity, while C−H and C−C groups show electrophilicity, which have electrostatic adsorption effect on negatively charged ClO 4 − anions to promote lithium salt dissociation [13] . Meanwhile, DMSO molecules with strong nucleophilic S=O groups are more involved in the first solvation sheath to bind with Li + [14] .…”
Section: Resultsmentioning
confidence: 99%
“…À anions to promote lithium salt dissociation. [13] Meanwhile, DMSO molecules with strong nucleophilic S=O groups are more involved in the first solvation sheath to bind with Li + . [14] To optimize the concentration of 18C6 additive, MD simulations of electrolytes containing 50 mM 18C6 (50-18C6) and 200 mM 18C6 (200-18C6) are given in Figure S4, and the CNs of different electrolytes are aggregated in Figure S5.…”
Section: Methodsmentioning
confidence: 99%
“…[17] Hou et al [18] identified solvent-assisted jumping as the main route of lithium-ion transport in the MOF-688 material and explained the key role of solvents. Yang et al [19] used the molecule-anion coordination to promote the dissociation of lithium salts, increase the concentration of free lithium ions, and achieve the fixation of anions, which weakened the dynamic traction of lithium ions when moving, and greatly enhanced the transport dynamics of lithium ions. He et al [20] developed a multispectral characterization strategy combined with first-principles calculations and found that the solvation structure and conduction mechanism of Li + in QSSEs were similar to those in highconcentration LEs.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al. [ 19 ] used the molecule‐anion coordination to promote the dissociation of lithium salts, increase the concentration of free lithium ions, and achieve the fixation of anions, which weakened the dynamic traction of lithium ions when moving, and greatly enhanced the transport dynamics of lithium ions. He et al.…”
Section: Introductionmentioning
confidence: 99%
“…With the ever-increasing demand for efficient and clean energy, electric energy has become the optimum alternative to traditional fossil energy . Lithium battery, as a clean and portable energy storage device, has been widely used in social production and life. However, most lithium batteries suffer from serious safety problems such as easy leakage, flammability, and explosion due to the used liquid electrolyte. With the progress of technology and the application of wearable electronic equipment, the demand for flexible high-energy devices has reached a zenith. By virtue of their outstanding safety, excellent flexibility, and high energy density, solid-state polymer electrolytes (SPEs) have evoked great interest of researchers. Compared with inorganic solid-state electrolytes with poor interface performance, difficulty to process, and high brittleness, SPEs show better processability for large-scale production.…”
Section: Introductionmentioning
confidence: 99%